2014
DOI: 10.1109/tmag.2013.2284934
|View full text |Cite
|
Sign up to set email alerts
|

A 3-D Semi-Implicit Method for Computing the Current Density in Bulk Superconductors

Abstract: LGEP 2014 ID = 1529International audienceA semi-implicit approach is proposed for computing the current density in superconductors characterized by nonlinear vectorial power law. A nodal discontinuous Galerkin method is adopted for the spatial discretization of the nonlinear system satisfied by the components of the electric field. Explicit developments are used to construct boundary conditions to avoid the modeling of a volume around the superconducting sample. A modified Newton iterative method is introduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…where the function E( j) characterizes the electromagnetic behavior of HTS films. As the function E( j), we assume the following power law [2][3][4][7][8][9][10]:…”
Section: Shielding Current Analysis Of Cracked Hts Film 21 Initial-mentioning
confidence: 99%
“…where the function E( j) characterizes the electromagnetic behavior of HTS films. As the function E( j), we assume the following power law [2][3][4][7][8][9][10]:…”
Section: Shielding Current Analysis Of Cracked Hts Film 21 Initial-mentioning
confidence: 99%
“…The numerical method used in this paper is the CVM recently published [7], [13]. The CVM can be regarded as a special version of the weighted residuals method.…”
Section: B Numerical Analysis Modelmentioning
confidence: 99%
“…A 3-D numerical model based on finite-element method have to face up the numerical oscillations that affect convergence properties. Different works based on flux approaches are introduced to handle theses convergence problem [7]- [9], [13]. Unfortunately, few of them are dedicated to study the thermomagnetic system that characterizes the superconductor materials.…”
Section: Introductionmentioning
confidence: 99%
“…We choose to solved this problem using an electric field formulation, indeed, it is not a usual way; however, some studies can be found [4][5][6].…”
Section: Introductionmentioning
confidence: 99%